Daily life stress and the cortisol awakening response over a 13-months stress period: findings from the LawSTRESS project - Giglberger, Marina; Peter, Hannah L.; Kraus, Elisabeth; Kreuzpointner, Ludwig; Zänkert, Sandra; Henze, Gina-Isabelle; Bärtl, Christoph; Konzok, Julian; Kirsch, Peter; Rietschel, Marcella; Kudielka, Brigitte M.; Wüst, Stefan (Psychoneuroendocrinology, 2022)
The LawSTRESS project is a controlled prospective-longitudinal study on psychological, endocrine, central nervous and genetic predictors of responses to long-lasting academic stress in a homogenous cohort. In this first project report, we focused on the association between daily life stress and the cortisol awakening response (CAR). The CAR, a distinct cortisol rise in the first 30-45 min after morning awakening, is a well-established marker of cortisol regulation in psychoneuroendocrinology. Law students from Bavarian universities (total n = 452) have been studied over a 13-months period at six sampling points starting 12 months prior exam. The stress group (SG) consisted of students experiencing a long-lasting and significant stress period, namely the preparation for the first state examination for law students. Law students assigned to the control group (CG) were studied over an equally long period without particular and sustained stress exposure. To investigate stress related alterations in the CAR, we examined a subsample of the LawSTRESS project consisting of 204 students with 97 participants from the SG (69.1% female, mean age = 22.84 ± 1.82) and 107 from the CG (78.5% female, mean age = 20.95 ± 1.93). At each sampling point, saliva samples for cortisol assessment were collected immediately upon awakening and 30 as well as 45 min later. Perceived stress in daily life was measured by repeated ambulatory assessments (about 100 queries over six sampling points). The time course of perceived stress levels in the two groups differed significantly, with the SG showing an increase in perceived stress until the exam and a decrease thereafter. Stress levels in the CG were relatively stable. The CAR was not significantly different between groups at baseline. However, a blunted CAR in the SG compared to the baseline measure and to the CG developed over the measurement timepoints and reached significance during the exam. Remarkably, this effect was neither associated with the increase in perceived stress nor with anxiety and depression symptoms, test anxiety and chronic stress at baseline. The present study successfully assessed multidimensional stress trajectories over 13 months and it documented the significant burden, law students preparing for the first state examination are exposed to. This period was related to a blunted CAR with presumed physiological consequences (e.g., on energy metabolism and immune function). Mean psychological stress levels as well as the CAR returned to baseline levels after the exam, suggesting a fast recovery in the majority of the participants.